Assessment of 2D-FET Based Digital and Analog Circuits on Paper. (November 2021) - Vatalaro, Massimo; De Rose, Raffaele; Lanuzza, Marco; Iannaccone, Giuseppe; Crupi, Felice
Abstract: Two-dimensional (2D) materials represent an emerging technology for transistor electronics in view of their attractive electrical and mechanical properties. This work investigates molybdenum disulfide (MoS2 ) based field-effect transistors (FETs) fabricated on paper substrate for designing both digital and analog circuits, such as inverter, current mirror, and Physical Unclonable Function (PUF) bitcell. Electrical measurements of fabricated devices are exploited to setup a look-up-table (LUT)-based Verilog-A model to be integrated in a commercial circuit simulator. Obtained results prove the potential of paper-based MoS2 FETs as building blocks of next-generation integrated circuits for a wide range of practical applications.